Digitalization of climate change communication: opportunities, challenges, and recommendations for Vietnam - Ta Van Viet; Luu Thi Thu Huyen; Dr. Chu Duc Ha; Vu Thi Minh Tam; Phan Thuy Linh (Journal of State Management, 2025)
This article assesses the role of digital communication in climate change discourse, analyzing how social media platforms, big data, artificial intelligence (AI), and data visualization are reshaping the dissemination and reception of climate change information. It also highlights the shift from traditional media to interactive models that foster public engagement through viral hashtags, activist campaigns, and emerging technologies. Based on an examination of global trends in the digitalization of climate change communication and an analysis of the current situation in Vietnam, the authors propose some recommendations to enhance the effectiveness of digital communication on climate change in the country. These recommendations aim to ensure that digital advancements support informed decision-making and meaningful action in response to climate change.